Aristotle’s Logic at the University of Buffalo’s Department of Philosophy (2009)
We begin with an introductory overview of contributions made by more than twenty scholars associated with the Philosophy Department at the University of Buffalo during the last half-century to our understanding and evaluation of Aristotle’s logic. More well-known developments are merely mentioned in order to make room to focus on issues at the center of attention from the beginning: existential import and, more generally, the analysis of categorical propositions. I include a list of the UB scholars, a list of collaborators and supporters from fellow institutions, a bibliography of relevant publications by UB scholars, and a bibliography of important related works.